Deteksi Boraks Pada Ikan Asin di Pasar Tradisional Kota Tanjung Balai Provinsi Sumatera Utara - Vera Ananda Harahap; Sartini Sartini; Ida Fauziah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2022)
Fish is a kind of easily-damaged raw food which mostly caused by microorganism i.e bacteria, mold and yeast. Fish salting is one of common applied preservation method to avoid bacterial contamination as decay prevention. Another common method is by adding borax in fish preservation process which can inhibit the growth of microorganism but it caused a negative effect for consummer’s health. The objective of this study is to examine the presence of borax in the salted fish that is marketed at the Tanjung Balai Traditional Market, North Sumatra Province. This study used a qualitative test method by testing the sample in the laboratory in accordance with the standards of the Regional Health Laboratory. The results of the qualitative test of borax on 30 samples of salted fish from the market revealed that none of samples altered the color of tumeric paper after being dipped in the sample solution. This finding indicated that all samples of salted fish contain no borax.